Solid Solution Series between CdIn2Te4 and AgInTe2 Investigated by Resonant X‐ray Scattering12. Issue 15 (23rd October 2014) - Welzmiller, Simon; Hennersdorf, Felix; Fitch, Andy; Oeckler, Oliver
Abstract AgInTe2 and CdIn2Te4 exhibit structures related to the chalcopyrite type. They form a solid solution (CdIn2Te4)x(Ag2In2Te4)1–x with a miscibility gap for 0.5 < x < 0.95. Such compounds are interesting for the application in solar cells or as thermoelectric materials. Joint refinements of high‐resolution synchrotron powder diffraction data for CdIn2Te4, Ag0.75Cd0.125InTe2 (x = 0.25) and Ag0.6Cd0.2InTe2 (x = 0.4) measured at the K‐absorption edges of Ag, Cd, In, Te and far away from these edges yield unambiguous information on the element and vacancy distribution. In CdIn2Te4, the vacancies are completely ordered and cadmium and indium are uniformly distributed over both cation positions. Ag0.75Cd0.125InTe2 and Ag0.6Cd0.2InTe2, which represent different Cd contents associated with different vacancy concentrations, exhibit disordered chalcopyrite‐type structures. The vacancies concentrate on the Ag position of AgInTe2 with additional Ag, Cd and little In, whereas the In position remains predominantly occupied by In, little Ag, and almost no Cd.